Istismar Zakat Funds in the Perspective of MUI Fatwa No. 4 of 2003: Implications For the Welfare of Mustahik - Muhlisah Hanifati; Nurkhalis Muchtar; M. Dawud Arif Khan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze in depth the Fatwa of the Indonesian Ulema Council (MUI) No. 4 of 2003 regarding the legality of the use of zakat funds for istismar activities (investment) and how it is implemented within the framework of the productive zakat utilization program at the Central National Amil Zakat Agency (BAZNAS). The main focus of this research includes deconstructing the understanding of the substance of fatwas, mapping implementation practices at the level of national zakat authorities, and projecting its impact on the escalation of mustahik welfare. Methodologically, this study applies a qualitative approach with a case study design through a structured interview method with policy makers at the Central BAZNAS and comprehensive documentation techniques. A normative juridical approach is applied to dissect secondary data and literature materials, which includes synchronization between national zakat laws and regulations and fatwas related to investment in religious social funds. An analysis was carried out on primary and secondary literature to present a holistic insight into zakat governance from the perspective of positive law and Islamic law. The results of the study revealed two fundamental findings: first, the Central BAZNAS institutionally has strategic potential in transforming zakat funds into productive investment instruments in accordance with the mandate of the fatwa to create economic added value. Second, even though the instruments and implementation plans have been carefully prepared, the Central BAZNAS has not officially executed the investment program until this research is completed. This phenomenon is in contrast to several BAZNAS at the regional level, such as West Java, which have accelerated through similar productive zakat programs. This emphasizes that the implementation of the istismar fatwa is highly dependent on the courage of institutional innovation, appropriate risk mitigation, and certainty of operational regulations.